Chorioamnionitis-Induced Immunological Changes and Neonatal Outcome - Awonuga, Modupe T.; Omar, Said A. (Journal of Pediatric Infectious Diseases, 2017)
Chorioamnionitis is inflammation of the fetal membranes (chorion and amnion) which could be of microbial or nonmicrobial etiology. It is a common complication of pregnancy with significant implications for both mother and infant. It represents a spectrum of diseases, which range from histological but subclinical chorioamnionitis to funisitis and chorionic vasculitis with multiorgan involvement in the fetus. Chorioamnionitis results in the activation of the fetal innate immune system known as the fetal inflammatory response syndrome (FIRS). FIRS with or without evidence of microbial presence initiates an inflammatory cascade that has been implicated in the mechanisms responsible for the fetal injury. Such injury can result in adverse neonatal outcomes involving multiple organ systems with high perinatal and long-term morbidity and mortality. While antimicrobial treatment of chorioamnionitis is beneficial to the mother, it is unclear whether the same holds true for the fetus as the damage may already be done by the production of proinflammatory cytokines. This article reviews the immunological changes and their consequences in neonates born to mothers with chorioamnionitis.
Keywords: chorioamnionitis; inflammation; cytokines; fetal inflammatory response syndrome; neonatal outcome